PERSEPSI ANAK PADA ACARA TELEVISI - Pradekso, Tandiyo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The poor quality of television program available to Indonesian children and the escalating cases of anti-social and delinquency among children are undeniably the hard fact. But linking the two in a causal relationship is a mere speculation that oversimplifying the issue. At the conceptual level in the study of mass communication, there are theories based on the perspective of the limited influence of the mass media. Theories such as those of Klapper’s phenomenistic, DeFleur’s individual differences and social category, selective processes theory, and Seymour Feshbach’s catharsis theory, are all discouraging the behavioral effect of mass communication.Media influence on children is determined by their comprehension in TV viewing. By about age 8 or 9 (Huston et.al), children are about as accurate as adults in judging whether a television program is presenting fiction or fact. There are arguments on how children perceive the reality out of the television. First, Aletha C. Huston explained that perceptions of reality occur on two dimensions: factuality and social realism. Second, Gunter and McAleer pointed out that children use three categories of television versus real-life comparisons. These include the category of the ‘actual’, the ‘possible’, and the ‘impossible’. The third explanation dealt with the way children evaluate characters in television programs.Findings revealed that perception on factuality was dominant in programs such as news, sports, infotainment, talk-show, variety-show, music, and reality-show. Perception of social realism was dominant in cartoons, movies, and soap-operas. Similar to those of factuality, the actual category appeared predominantly in news, sports, religion, talk-show, variety-show, music, and reality-show. The possible was slightly highlighted in cartoons, movies, and soap-operas. While the impossible also seemed dominant in cartoons, movies, and soap-operas.Conceptually, the 4 children’s favorite characters are the humor of the characters; the strength of the characters; the attractiveness of the characters; and the activity level of the characters. Humor was dominant in cartoons, talk-show, and variety-show. Strength was central in sports and movies, and attractive in infotainment and talk-show. There were no active characters significantly perceived in any television programs.